Documentazione & Digitale 2020 Rome, Knowledge and communication of Cultural Heritage (diségno, 2021)
The event presented by the Department of History, Design and Restoration of Architecture of Sapienza University of Rome, and sponsored by UID Unione Italiana per il Disegno [1], is a moment of exchange and scientific and cultural update; the event is in its third edition after the previous editions held at the University of Pavia and the Politecnico di Torino (read more).